Mulheres agricultoras familiares, políticas públicas de crédito e a Agenda 2030: desafios na promoção da igualdade de gênero - Almeida, Josiane Patricia Fritz (2024)
The aim of the research was to understand how women in family farming relate to credit policies and how these interactions can contribute to promoting gender equality, in line with the principles established by the 2030 Agenda. In the first article, the analysis focuses on studying the current situation of rural women in terms of social issues, access to rural credit and how they manage their properties. Conducted in the region of COREDE Rio da Várzea, RS, the study reveals significant disparities in the distribution of Pronaf Aptitude Declarations (DAPs) between genders and in the levels of access to financing. Municipalities such as Chapada show a predominance of male DAPs, while others, such as Palmeira das Missões, show greater female representation. The analysis highlights the need for policy interventions to promote gender equity in access to financial resources, with a view to guaranteeing fair opportunities for men and women in agricultural and rural economic development. The second article addresses the issue of rural women's anonymity in relation to gender equality for the fulfillment of Goal 5 of the 2030 Agenda. It highlights the crucial importance of gender equality in agriculture and sustainable development, backed up by data on agricultural occupation in Brazil and the involvement of women in this sector. Despite women's significant contribution to food production, they still face challenges in gaining recognition and participation in decision-making spaces. Although many women are involved in agricultural activities, few hold leadership positions or have an active voice in political and social contexts. The studies carried out in this dissertation highlight that women's participation in family farming and their access to credit policies are crucial aspects for achieving gender equality and promoting sustainable development, as advocated by the 2030 Agenda. The results highlight the urgent need for specific policy interventions and programs that recognize and address gender disparities, guaranteeing the economic empowerment of rural women and their full participation in the decisions that affect their lives and communities. Equal opportunities and equitable access to financial resources, education and opportunities are not only issues of social justice, but also fundamental to building a fairer and more prosperous society for all.